Professional communication skills training for students of faculty of Physical Education and Sports - Alexander V. Levchenko; Natalia V. Mayorova (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The article is devoted to the problem of the academic communication skills development and describes the importance of studying a foreign language for students of non-linguistic universities. Today, academic communication, and in particular professional communication skills, as part of it, is becoming the subject of study of theorists and practitioners. Proficiency in a foreign language is a professionally significant property of any person who is preparing to work in a global society. Academic interaction at the international level is already considered as a mandatory component of the life of a modern student.Thus, communication in English in the student international environment and the participation in academic exchange programs are the main types of studying and are considered in the content of the “professional portrait” of a specialist in physical education and sports as system forming. The authors experimentally show the characteristics which can be developed on the basis of a significant program for teaching a foreign language at the faculty of physical education. The definition of the concept of “professional portrait” of a specialist in physical education and sports is given, in which professional communication skills in a foreign language plays a special role.